Carcass wrote:

If 3(x + 2) = x — 4, then x =

(A) —5

(B) —3

(C) 1

(D) 3

(E) 5

Kudos for R.A.E

Alternatively, we can

test the answer choices by plugging the x-values into the given equation.

(A) —5

Let's take the given equation and replace x with

-5 We get: 3(

-5 + 2) =

-5 — 4

Evaluate the part in the brackets to get: 3(-3) =

-5 — 4

Evaluate both quantities: -9 = -9

Perfect - it works!!

Answer: A

Cheers,

Brent

_________________

Brent Hanneson – Creator of greenlighttestprep.com

Sign up for our free GRE Question of the Day emails